Effects of Intermittent Hypoxia on Expression of Glucose Metabolism Genes in MCF7 Breast Cancer Cell Line - Jarrar, Yazun; Zihlif, Malek; Al Bawab, Abdel Qader; Sharab, Ahmad (Current Cancer Drug Targets, 2020)
Background: Hypoxic condition induces molecular alterations which affect the survival rate and chemo-resistant phenotype of cancer cells. Objective: The aim of this study is to investigate the influence of intermittent hypoxic conditions on the expression of glucose metabolism genes in breast cancer MCF7 cell line. Methods: The gene expression was analyzed using a polymerase chain reaction-array method. In addition, the cell resistance, survival and migration rates were examined to assure the hypoxic influence on the cells. Results: 30 hypoxic episodes induced the Warburg effect through significant (p-value < 0.05) upregulation of the expression of PCK2, PHKG1, ALDOC, G6PC, GYS2, ALDOB, HK3, PKLR, PGK2, PDK2, ACO1 and H6PD genes that are involved in glycolysis, were obtained. Furthermore, the expression of the major gluconeogenesis enzyme genes was significantly (ANOVA, p-value < 0.05) downregulated. These molecular alterations were associated with increased MCF7 cell division and migration rate. However, molecular and phenotypic changes induced after 30 episodes were normalized in MCF7 cells exposed to 60 hypoxic episodes. Conclusion: It is concluded, from this study, that 30 intermitted hypoxic episodes increased the survival rate of MCF7 breast cancer cells and induced the Warburg effect through upregulation of the expression of genes involved in the glycolysis pathway. These results may increase our understanding of the molecular alterations of breast cancer cells under hypoxic conditions.
Keywords: MCF7 cells